Improving the Personnel Administration System as a Pillar of Employee Welfare at the Regional Personnel Agency of East Tanjung Jabung - Sukri, Sukri; Abidin, Zaenal; Wandi, Wandi; Marwendi, Reza Okva (Zabags International Journal of Engagement, 2024)
This research aims to improve the personnel administration system at the East Tanjung Jabung Regional Civil Service Agency as the main pillar of employee welfare. With a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and document analysis. The findings of the study show that the administrative system that is still manual, the limitations of technological infrastructure, the lack of officer skills, and the absence of a structured Standard Operation Procedure are the main obstacles in personnel management. As a result, the administrative process runs slowly, inefficiently, and often causes delays in the fulfillment of employee rights. To overcome this problem, it is recommended to implement a digital-based administrative system, intensive training for administrative officers, the preparation of clear Standard Operating Procedures, and the strengthening of technological infrastructure and transformational leadership. With the implementation of these measures, it is hoped that the Regional Civil Service Agency can provide more efficient, accurate, and responsive administrative services, thereby supporting the overall welfare of employees